Pengembangan Aplikasi Pemesanan Kopi di Wilayah Cikampek Berbasis Android - Rahmawati, Muthia Fidiasari (UNIVERSITAS KALBIS, 2025)
This study discusses how to design and build a coffee ordering application at an Andorid-based coffee shop and to develop a drink order application so that it is easy for customers to order drinks online. The method used in application development is the Prototyping Method with Unified Modeling Language (UML). The application built is an Android-based application for ordering coffee in the Cikampek area. This admin version of the application, users must create category menu names, drink menus and update delivery orders to customers. While the customer version of this application, users can buy one or more drinks they want. The result of this research is an android-based application for ordering coffee in the Cikampek area.